The dojima rice exchange : From rice trading to index futures trading in Edo-period Japan - Takatsuki, Yasuo; Rubinfien, Louisa (Tokyo Japan publishing industry coundation for culture, 2022)
The book explores the Dojima Rice Exchange in Osaka during Japan's Edo period (1603-1868), often regarded as the world's first futures trading market. It examines how this innovative market for rice certificates and index futures operated, its remarkable impact on the contemporary economy, and the challenges it faced. Through the story of Dojima's development and regulation, the book reveals fundamental insights into the nature and continuity of market dynamics over time.
Includes bibliographical references and index
Keywords: Tài chính - Ngân hàng